Improving customer-focused marketing capabilities and firm financial performance via marketing exploration and exploitation - Vorhies, Douglas W.; Orr, Linda M.; Bush, Victoria D. (Journal of the Academy of Marketing Science, 2011)
Evidence within the marketing literature has shown that marketing capabilities are important drivers of firm performance. However, very little is known about how firms improve their marketing capabilities via the embedding of new market knowledge. Organizational learning theory provides us with a theoretical lens through which we can examine how existing customer-focused marketing capabilities may be improved and new customer-focused marketing capabilities may be created via marketing exploitation and exploration capabilities. In addition, this study investigates whether ambidexterity in marketing exploration and exploitation exists and finds that firms cannot do both at high levels without risking a negative impact on customer-focused marketing capabilities. This study also presents findings demonstrating how improving the two customer-focused marketing capabilities in our study, brand management and customer relationship management, impacts objective financial performance.